REKONSTRUKSI KECAKAPAN SOSIAL GURU DALAM PENGEMBANGAN BERBICARA ANAK USIA DINI - Gian Fitria Anggraini; Ari Sofia (Jurnal Ilmiah Visi, 2016)
Social interaction is an early foundation for children to learn recognizing their surrounding environment. This study aimed to examine the relationship and contribution of teacher social skill in interaction between children through language development, especially speaking in early ages. The research was conducted I Bandar Lampung as from September through October 2015. The research subjects were 30 early childhood teachers in Bandar Lampung, which was carried out through purposive sampling technique. The research method was conducted with a quantitative approaches-regression method. The data was collected through a questionnaire and was analyzed by using simple linear regression analysis. The results showed a regression coefficient between variables for 0,511, with a significance value of 0,003. Interaction performed deeply by teachers on children has a significant influence to the children’s speak development. Although the contribution has not been adequate, it indicates that the quality and quantity of interaction between teachers and children needs to be increased.